Penerapan Lelang Non Eksekusi Sukarela Online oleh Pejabat Lelang Kelas II (Studi Kasus Kantor Pejabat Lelang Kelas II Rosalinda, SH) - giofanny, putri rahma; Hasibuhan, Abdul Lawali; Mina, Revi Fauzi Putra (Universitas Medan Area, 2024)
The purpose of this study is to find out the Mechanism of Implementing Online Voluntary Non-Execution Auctions and Analysis of the Application of Online Voluntary Non-Execution auctions Methods by Class II Auction Officials on movable objects. This study uses a normative juridical method with an analytical descriptive approach to analyze the implementation of online voluntary non-execution auctions at the Office of Class II Auction Officials Rosalinda, SH, through literature research, field, and interviews. The results of the study show that the implementation of voluntary non-execution auctions online reflects digital transformation in a more efficient, transparent, and inclusive auction system. Based on PMK Number 213/PMK.06/2020, this auction is carried out voluntarily with a closed bidding mechanism for privacy or open bidding for real-time competition. Key advantages include time efficiency, information disclosure, and wide access without geographical restrictions. Challenges such as data security and technological infrastructure remain a concern, but the implementation by Class II Auction Officials, such as in Rosalinda's Office, SH, is a successful example of the modernization of technology-based auction systems.